A “σ-Hole”-Containing Volatile Solid Additive Enabling 16.5% Efficiency Organic Solar Cells - Fu, Jiehao; Chen, Shanshan; Yang, Ke; Jung, Sungwoo; Lv, Jie; Lan, Linkai; Chen, Haiyan; Hu, Dingqin; Yang, Qianguang; Duan, Tainan; Kan, Zhipeng; Yang, Changduk; et al. (iScience, 2020)
Here we introduce a σ-hole-containing volatile solid additive, 1, 4-diiodotetrafluorobenzene (A3), in PM6:Y6-based OSCs. Aside from the appropriate volatility of A3 additive, the synergetic halogen interactions between A3 and photoactive matrix contribute to more condensed and ordered molecular arrangement in the favorable interpenetrating donor/acceptor domains. As a result, greatly accelerated charge transport process with suppressed charge recombination possibility is observed and ultimately a champion PCE value of 16.5% is achieved. Notably, the A3 treated OSCs can maintain a high efficiency of over 16.0% in a wide concentration range of A3 additive between 10 and 35 mg/mL. The A3-treated device shows excellent stability with an efficiency of 15.9% after 360-h storage. This work demonstrates that the σ-hole interaction can be applied to enhance the OSC performance and highlights the importance of non-covalent interactions in the optoelectronic materials. [Display omitted] •A "σ-hole”-containing small molecule is used as an additive for organic solar cells•16.5% efficiency organic solar cells are achieved with additive engineering•Excellent stability and easy processability are obtained with the additive Energy Materials; Organic Chemistry; Supramolecular Chemistry